Role of Character Education in National Character Building: A Retrospection Noble Values of Muslim Religiosity - Hakim, Alif Lukmanul (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
Indonesia is widely known as one accumulated national entity consisting of many differences of tribes, cultures and religions. As a result of unity in diversity, Indonesia possessed a significant impact in the history aiming to educate youth generations. The article describes a historical background of the nation running education specifically to build the nation character. Meanwhile based on that reason, the effort to implement trustworthy behaviors through whole aspect of religious characteristics imprinted in the deep heart of the nation. To add some more, Indonesia which is well-known for its addressing religious nation must set up the goal of the nation which is definitely in harmony with the values of religious teachings. The article also provides an effort to educate the nation by focusing and paying great attention to the program of civilizing people. Clearly, the article in detail discusses a successful progress of bulding character education in Indonesia. Besides, this article utilizes analysis methid focusing on causal effectual method correlating Character Education as a result of national character building using literature review model. This article then finds out that there is a similar pattern between bulding nation character and character education. Moreover, the term retrospection is used merely to reflect the implementation of noble values of Indonesia through what is called by education principle.   Keywords: Retrospection, Educarion, Character